Clinical Performance Comparison of Two In-Vitro Diagnostic Multivariate Index Assays (IVDMIAs) for Presurgical Assessment for Ovarian Cancer Risk - Shulman, Lee P.; Francis, Marra; Bullock, Rowan; Pappas, Todd (Advances in therapy, 2019)
Introduction Adnexal or pelvic mass is a finding that commonly raises suspicion for malignancy, especially for ovarian cancer. Proper identification prior to surgery would permit appropriate referral to a specialty center in cases likely to be ovarian cancer, as optimal outcomes in such cases are obtained when surgical staging and treatment are provided at the time of initial surgery. Methods We compared the screening capabilities of two in vitro diagnostic multivariate index assays (IVDMIAs), a new IVDMIA (second-generation multivariate index assay: MIA2G) and a currently used triage algorithm (Risk of Ovarian Malignancy Assay: ROMA). Results Among 245 subjects (24.7%) determined to have a malignancy, ROMA misclassified 51 malignancies (including 10 high-grade ovarian malignancies), whereas MIA2G misclassified 22 (including 5 high-grade ovarian malignancies). Early stage cancers were more frequently misclassified by ROMA (20 vs. 8 cases). The rate of “test-negative” malignancies was significantly higher for ROMA, while the rate of “test-positive” benign cases was significantly higher for MIA2G. Conclusion Triage algorithms play an important role in improving clinical outcomes for women presenting with an adnexal mass regardless of the eventual diagnosis. In this study, MIA2G was shown to correctly predict more cases of ovarian cancer than the ROMA algorithm. Funding Aspira Labs/Vermillion Inc.